The Influence of Emotional Intelligence, Work Environment, and Work Culture on Employee Performance at the Office of Investment and Integrated One-Stop Service, Bantaeng Regency - Isnawati Isnawati; Edi Jusriadi; Muchriady Muchran (Green Publisher Indonesia, 2024)
This research aims to find out, analyze and explains the Influence of Emotional Intelligence, Work Environment, and Work Culture on Employee Performance at the Plantation Service Office Capital and One Stop Integrated Services in Bantaeng Regency. Type This research is quantitative research with a sample of 49 respondents using questionnaires as a source of collection data, the analysis used is Multiple Linear Regression Analysis by using the SPSS 24 application. The research results show that, emotional intelligence positive and significant effect on employee performance, the environment Work has a positive and significant influence on employee performance and culture Work has a positive and significant effect on employee performance.